Ultrasonographic Measurement of Palatine Tonsil Size and Its Correlation with Body-Mass Index and Hepatosteatosis in Adolescents (Annals of Medical Research, 2021)
Aim: To research the correlation between body-mass index (BMI) and hepatosteatosis with palatine tonsil size measured using transcervical ultrasonography (TCU) in adolescents.